PENGARUH METODE DEMONSTRASI TERHADAP PERILAKU SADARI SEBAGAI UPAYA DETEKSI DINI KANKER PAYUDARA DI PUSKESMAS KEDURUS - Rachmawati Ika Sukarsih (Sinar : Jurnal Kebidanan, 2019)
Objective:to know the effect of demonstration method of SADARI toearly detection of breast cancer Methods: This study used pre experimental design with a sample of women reaching 30-45 years as many as 35 people. Data were analyzed with the Wilcoxon Sing Rank Test with Î± 0.05, the results obtained p of 0.00. Results: This states that the Demonstration Method Against Conscious Behavior as an Early Detection for Breast Cancer in the Kedurus Health Center. The Demonstration Method is learning by pointing at objects that encourage appropriate shapes and the audience can be used easily and can be used by other women who have not been able. Conclusion: The conclusions of this research are demonstration method of SADARI effective for early detection of breast cancerKeywords: Demonstration Method, attitude, breast cancerÂ